2019
DOI: 10.1016/j.joule.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Quinone-Based Redox Mediator to Facilitate Li2S Oxidation in Li-S Batteries

Abstract: We utilized quinone redox chemistry to design a new RM for fast and stable cycling of Li-S batteries. Through rational tuning of the redox potential, stability, and solubility of quinones by molecular engineering, we successfully demonstrated that the quinone redox can facilitate the Li 2 S oxidation and the maintained Li 2 S original morphology. The introduction of AQT as an RM is a simple and effective approach to significantly enhance multiple aspects of sulfur redox chemistry under challenging conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
186
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(197 citation statements)
references
References 52 publications
2
186
0
Order By: Relevance
“…b) Schematic illustration of direct Li 2 S oxidation and RM‐assisted Li 2 S oxidation in Li–S battery. Reproduced with permission . Copyright 2019, Elsevier.…”
Section: The Catalysis Of Li–s Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…b) Schematic illustration of direct Li 2 S oxidation and RM‐assisted Li 2 S oxidation in Li–S battery. Reproduced with permission . Copyright 2019, Elsevier.…”
Section: The Catalysis Of Li–s Chemistrymentioning
confidence: 99%
“…Three types of RM were chosen as the representatives according to different oxidization potential compared with active materials, namely, cobaltocene ( E RM < E Li2S ), dibenzenechromium ( E RM ≈ E Li2S ), and decamethylferrocene/LiI/ferrocene ( E RM > E Li2S ). It was found that RM with higher redox potential than Li 2 S could promote the oxidation of Li 2 S 2 /Li 2 S into LiPSs, wherein as‐produced LiPSs could also serve as RM to facilitate the conversion of Li 2 S. Recently, Tsao et al proposed the design rationales of the RM for the Li 2 S cathode (Figure b) . The RM with appropriate redox potential was first electrochemically oxidized to RM + , which can chemically oxidize Li 2 S over the whole surface and further electrochemically reoxidized after diffusing to the surface of conductive host.…”
Section: The Catalysis Of Li–s Chemistrymentioning
confidence: 99%
“…Reproduced with permission. [ 234 ] Copyright 2019, Elsevier. c) Energy levels of FMOs for Li 2 S x and DBBQ‐Li 2 S x .…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…[ 236 ] They enable the redox of insoluble species to be coupled to the electrode surface without requiring electronic contact (Figure 15b). [ 234 ] An RMs with proper equilibrium potential ( E RMs < E Li2S ) can address the sluggish kinetic in Li–S batteries by redox‐mediated process. The study of employing RMs in Li–S system is still in infant, but the role of RMs in regulating the S redox reactions has been verified.…”
Section: Optimization Strategies Of Redox Reactionmentioning
confidence: 99%
“…Li/Li + )r edox pairs is expected to maintain the longevity of rechargeable Li-S batteries. [9] Inorganic RMs such as iodine/iodide and the metallocene derivates have been proved effective in oxidizing the dead Li 2 S. [10] Meanwhile,o rganic RMs hold advantages of tunable redox potentials and electrochemical stabilities.V arious molecules such as conjugated quinones, [11] Schiff bases, [12] disulfide organics, [8] metallocene,and imides [13] have been successfully adopted.…”
Section: Introductionmentioning
confidence: 99%